The Effect of Zig-Zag Running Training Using Weights on Dribbling Skills in Football Games for Extracurricular Students at Sma Negeri 6 Bengkulu Selatan - Fedho Frananda; Lina Tri Astuty B Sembiring; Martiani Martiani (Sinar Sport Journal, 2023)
This study aims to determine the effect of zig zag running exercises using weights on dribbling skills in soccer games for extracurricular students at SMA Negeri 6 Bengkulu Selatan. The type of research used in this study is a quantitative experimental research one Group pretest-posttest design. The population in this study were all extracurricular members at SMA Negeri 6 Bengkulu Selatan, amounting to 25 people or students. The results of the research on the effect of zig zag running exercises using weights on dribbling skills in soccer games for extracurricular students of SMA Negeri 6 Bengkulu Selatan obtained an average pretest result of 46.08 and an average Posttest result of 48.52 with a difference of 2.44 and the result of tcount is 10.16 > from ttable of 1.71008. Based on the statistical test with = 5% (0.05) that Ho is rejected or accepted Ha systematically that the Zig-zag running exercise has an effect on Dribbling skills.